Dissociation of LAG-3 inhibitory cluster from TCR microcluster by immune checkpoint blockade - Hashimoto-Tane, Akiko; Bowman, Edward P.; Sakuma, Machie; Yoneda, Natsumi; Yugi, Katsuyuki; de Waal Malefyt, Rene; Saito, Takashi (Frontiers in Immunology, 2024)
Lymphocyte activation gene (Lag)-3 is an inhibitory co-receptor and target of immune checkpoint inhibitor (ICI) therapy for cancer. The dynamic behavior of Lag-3 was analyzed at the immune synapse upon T cell activation to elucidate Lag-3 inhibitory mechanism. Lag-3 formed clusters and co-localized with TCR-microcluster (MC) upon T cell activation similar to PD-1. Lag-3 blocking antibodies (Ab) inhibited the co-localization between Lag-3 and TCR-MC without inhibiting Lag-3 cluster formation.Lag-3 also inhibited MHC-II-independent stimulation and Lag-3 Ab which did not block MHC-II binding yet could still block Lag-3's inhibitory function suggesting that the Lag-3 Ab blocks the Lag-3 inhibitory signal by dissociating the co-assembly of TCR-MC and Lag-3 clusters. Consistent with the combination benefit of PD-1 and Lag-3 Abs to augment T cell responses, bispecific Lag-3/PD-1 antagonists effectively inhibited both cluster formation and co-localization of PD-1 and Lag-3 with TCR-MC. Therefore, Lag-3 inhibits T cell activation at TCR-MC and the target of Lag-3 ICI is to dissociate the co-localization Lag-3 with TCR-MC.